2017
DOI: 10.1016/j.ebiom.2017.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine, a FDA-approved Drug, Prevents Zika Virus Infection and its Associated Congenital Microcephaly in Mice

Abstract: Zika virus (ZIKV) has become a global public health emergency due to its rapidly expanding range and its ability to cause severe congenital defects such as microcephaly. However, there are no FDA-approved therapies or vaccines against ZIKV infection. Through our screening of viral entry inhibitors, we found that chloroquine (CQ), a commonly used antimalarial and a FDA-approved drug that has also been repurposed against other pathogens, could significantly inhibit ZIKV infection in vitro, by blocking virus inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
124
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(129 citation statements)
references
References 39 publications
4
124
0
1
Order By: Relevance
“…Our data show that bafilomycin A1 strongly impairs the entry of ZIKV Uganda 976 (known to cause only mild symptoms) and ZIKV French Polynesia PF13/251013-18 (associated with neurological complications) in A549 and in SH-SY5Y cells. These data are in line with previous observations describing that ammonium chloride and chloroquine have the potential to block ZIKV infection [38][39][40]. It also reflects the observations that the infection process of a variety of other flaviviruses, such as dengue virus or West Nile virus, can be inhibited by preventing the receptor-mediated endocytosis.…”
Section: Discussionsupporting
confidence: 92%
“…Our data show that bafilomycin A1 strongly impairs the entry of ZIKV Uganda 976 (known to cause only mild symptoms) and ZIKV French Polynesia PF13/251013-18 (associated with neurological complications) in A549 and in SH-SY5Y cells. These data are in line with previous observations describing that ammonium chloride and chloroquine have the potential to block ZIKV infection [38][39][40]. It also reflects the observations that the infection process of a variety of other flaviviruses, such as dengue virus or West Nile virus, can be inhibited by preventing the receptor-mediated endocytosis.…”
Section: Discussionsupporting
confidence: 92%
“…Chloroquine is a widely used anti-malarial with immunomodulatory effects [1][2][3][4][5]. In a recent in vitro study chloroquine was found to inhibit the growth of SARS-CoV-2 in vitro [6].…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro antiviral activity of chloroquine has been identified since the late 1960's (Inglot, 1969;Miller and Lenard, 1981;Shimizu et al, 1972) and the growth of many different viruses can be inhibited in cell culture by both chloroquine and hydroxychloroquine, including the SARS coronavirus (Keyaerts et al, 2004). Some evidence for activity in mice has been found for a variety of viruses, including human coronavirus OC43 (Keyaerts et al, 2009), enterovirus EV-A71 (Tan et al, 2018), Zika virus (Li et al, 2017) and influenza A H5N1 (Yan et al, 2013). However, chloroquine did not prevent influenza infection in a randomized, double-blind, placebo-controlled clinical trial (Paton et al, 2011), and had no effect on dengue-infecteds patient in a randomized controlled trial in Vietnam (Tricou et al, 2010).…”
mentioning
confidence: 99%